2021
DOI: 10.5586/aa.7414
|View full text |Cite
|
Sign up to set email alerts
|

Micromorphological Characteristics of Fruit Surfaces of Some Usable Species of the Genus Valeriana (Valerianaceae) Among Ukrainian Flora

Abstract: The micromorphological features of the fruit surfaces of nine species of Ukrainian flora, namely Valeriana tuberosa L., Valeriana tripteris L., Valeriana rossica P. Smirn., Valeriana stolonifera Czern., Valeriana grossheimii Worosch, Valeriana sambucifolia Mikan fil., Valeriana officinalis L. s. str., Valeriana wolgensis Kazak. [ Valeriana officinalis var. nitida (Kreyer) Rostanski], and Valeriana simplicifolia (Rchb.) Kaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…ruber . The morphological characteristics of the flowers, fruits, microscopic structure of the epidermis (on the leaf, stem, and fruits), and pollen in species belonging to the genus Centranthus , are of taxonomic significance [ 62 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ruber . The morphological characteristics of the flowers, fruits, microscopic structure of the epidermis (on the leaf, stem, and fruits), and pollen in species belonging to the genus Centranthus , are of taxonomic significance [ 62 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study also revealed the characteristics of the exocarp in the fruits of C. kellereri and compared them with those in C. ruber. The morphological characteristics of the flowers, fruits, microscopic structure of the epidermis (on the leaf, stem, and fruits), and pollen in species belonging to the genus Centranthus, are of taxonomic significance [62][63][64].…”
Section: Morphological Analysis By Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
See 1 more Smart Citation